Myasthenia and risk of cancer: a population‐based case–control study. (26th February 2014) - Pedersen, E. G.; Pottegård, A.; Hallas, J.; Friis, S.; Hansen, K.; Jensen, P. E. H.; Gaist, D.
<x xml:space="preserve">Abstract</x> Background and purpose To evaluate the association between having non‐thymoma myasthenia and the risk of extra‐thymic cancer in a population‐based setting. Methods A nationwide case–control study was conducted in Denmark based on medical registries. The study included all cases with a first time diagnosis of cancer during 2000–2009. Each case was matched by birth year and gender with eight population controls using risk set sampling. Subjects with myasthenia were identified through a validated register‐based algorithm. Conditional logistic regression was used to compute crude and adjusted odds ratios (ORs), with 95% confidence intervals (CIs), for cancer associated with a prior diagnosis of myasthenia. Results In all, 233 437 cases and 1 867 009 controls were identified. A total of 80 cases and 518 controls had a prior diagnosis of myasthenia. Myasthenia was not associated with an increased risk of overall cancer (OR 1.1; 95% CI 0.9–1.4). Adjusted ORs for major cancer sites were also close to unity, whereas an elevated risk of lymphomas was observed (OR 2.0; 95% CI 0.8–5.5). Early‐onset myasthenia was associated with a slightly increased OR for overall cancer (1.5; 95% CI 1.0–2.3); however, this estimate was based on small numbers. Conclusions Non‐thymoma myasthenia was not associated with an increased risk of overall cancer. Larger studies are necessary to evaluate the association between myasthenia and risk of lymphoma and the potential effect modification by age of myasthenia onset in relation to cancer risk.